Regression Modelling Wih Spatial and Spatial-Temporal Data a Bayesian approach - Haining, Robert P.; Li, Guangquan, 1982- (Boca Raton : CRC Press LLC, 2020)
Modelling Spatial and Spatial-Temporal Data: A Bayesian Approach is aimed at statisticians and quantitative social, economic and public health students and researchers who work with spatial and spatial-temporal data. It assumes a grounding in statistical theory up to the standard linear regression model. The book compares both hierarchical and spatial econometric modelling, providing both a reference and a teaching text with exercises in each chapter. The book provides a fully Bayesian, self-contained, treatment of the underlying statistical theory, with chapters dedicated to substantive applications. The book includes WinBUGS code and R code and all datasets are available online. Part I covers fundamental issues arising when modelling spatial and spatial-temporal data. Part II focuses on modelling cross-sectional spatial data and begins by describing exploratory methods that help guide the modelling process. There are then two theoretical chapters on Bayesian models and a chapter of applications. Two chapters follow on spatial econometric modelling, one describing different models, the other substantive applications. Part III discusses modelling spatial-temporal data, first introducing models for time series data. Exploratory methods for detecting different types of space-time interaction are presented followed by two chapters on the theory of space-time separable (without space-time interaction) and inseparable (with space-time interaction) models. An applications chapter includes: the evaluation of a policy intervention; analysing the temporal dynamics of crime hotspots; chronic disease surveillance; and testing for evidence of spatial spillovers in the spread of an infectious disease. A final chapter suggests some future directions and challenges.
3 The Nature of Spatial and Spatial-Temporal Attribute Data -- 3.1 Introduction -- 3.2 Data Collection Processes in the Social Sciences -- 3.2.1 Natural Experiments -- 3.2.2 Quasi-Experiments -- 3.2.3 Non-Experimental Observational Studies -- 3.3 Spatial and Spatial-Temporal Data: Properties -- 3.3.1 From Geographical Reality to the Spatial Database -- 3.3.2 Fundamental Properties of Spatial and Spatial-Temporal Data -- 3.3.2.1 Spatial and Temporal Dependence -- 3.3.2.2 Spatial and Temporal Heterogeneity -- 3.3.3 Properties Induced by Representational Choices
Description based upon print version of record.
3.3.4 Properties Induced by Measurement Processes
OCLC-licensed vendor bibliographic record.
Keywords: Spatial analysis (Statistics); Regression analysis; Bayesian statistical decision theory; MATHEMATICS / Probability & Statistics / General